Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ajhb.22626
|View full text |Cite
|
Sign up to set email alerts
|

Determining osteoporosis risk in older Colono adults from rural Amazonian Ecuador using calcaneal ultrasonometry

Abstract: Objective Low bone density and osteoporosis prevalence, while well-documented in wealthy nations, are poorly studied in rural, non-clinical contexts in economically-developing regions such as Latin America. This study contributes preliminary osteoporosis risk data for a rural Colono (mestizo) population from Amazonian Ecuador. Methods Anthropometrics were collected for 119 adult participants (74 females, 45 males [50–90 years old]). Heel bone density and T-scores were recorded using calcaneal ultrasonometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…With society's trending toward aging and unhealthy lifestyle changes (such as high heat, high fat food intake increase and reduction in physical activity), the prevalence rate of essential hypertension (EH) and osteoporosis (OP) increases every year, and these have become two of the most common diseases in the world [ 1 3 ]. Research has shown that the number of fractures related to osteoporosis has reached approximately 1500000 each year in the United States [ 4 , 5 ]. In China, the population of people over 60 years old has been estimated as high as one hundred thirty-two million, and of these, approximately 90000000 patients have been diagnosed with osteoporosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With society's trending toward aging and unhealthy lifestyle changes (such as high heat, high fat food intake increase and reduction in physical activity), the prevalence rate of essential hypertension (EH) and osteoporosis (OP) increases every year, and these have become two of the most common diseases in the world [ 1 3 ]. Research has shown that the number of fractures related to osteoporosis has reached approximately 1500000 each year in the United States [ 4 , 5 ]. In China, the population of people over 60 years old has been estimated as high as one hundred thirty-two million, and of these, approximately 90000000 patients have been diagnosed with osteoporosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries and preindustrial societies, determinants and consequences of osteoporosis are poorly understood, although lower life expectancies may contribute to lower population prevalence of osteoporosis and absolute fracture risk due to mortality selection and young age structure . A recent study of rural agrarian Ecuadorians indicates a considerable prevalence of adults aged 50+ years with reduced bone status (43% women, 18% men), suggesting high osteoporosis risk despite a physically active lifestyle. In vivo studies in preindustrial societies are necessary to understand the ecological and energetic constraints under which human bones evolved.…”
Section: Introductionmentioning
confidence: 99%
“…A number of basic questions about bone biology have not yet been answered despite steady progress in the epidemiology and treatment of osteoporosis (Bartl & Frisch, 2009;Madimenos, Liebert, Cepon-Robins, Snodgrass, & Sugiyama, 2015;Marcus, Dempster, Cauley, & Feldman, 2013). This lack of insight into the factors that affect bone metabolism stems from a narrow focus on clinical settings in the context of wealthy nations, as well as the lack of fieldfriendly techniques to measure biomarkers of bone formation and resorption.…”
mentioning
confidence: 99%
“…This lack of insight into the factors that affect bone metabolism stems from a narrow focus on clinical settings in the context of wealthy nations, as well as the lack of fieldfriendly techniques to measure biomarkers of bone formation and resorption. The impact of the availability of these technologies is exemplified by the development of portable calcaneal ultrasonometers to measure bone mineral density; use of these ultrasonometers allowed researchers to obtain high-quality data on bone health in rural, isolated populations, namely indigenous Shuar and nonindigenous Colono from Ecuador (Madimenos et al, 2011(Madimenos et al, , 2015 and the Tsimane of Bolivia (Stieglitz et al, 2015;Stieglitz, Trumble, Kaplan, & Gurven, 2017).…”
mentioning
confidence: 99%